Impact of standardized methods on representativity in pancreato-biliary cytopathology Auswirkung standardisierter Aufarbeitungsmethoden auf die Befundqualität in der Pankreaszytologie - Veits, L.; Sterlacci, W.; Vieth, M. (Endoskopie heute, 2014)
Cytopathology is a very specific method in the diagnosis of malignant lesions of the pancreas, but the rate of non diagnostic material obtained by EUS-guided fine needle aspiration tends to be high. Our data show that the rate of diagnostic samples can be increased by standardization of the diagnostic process.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Cytology; Cytopathology; FNA; Pancreas